IMPLEMENTASI PENDEKATAN ETNOMATEMATIKA BERBASIS BUDAYA NIAS DALAM PEMBELAJARAN MATEMATIKA - Ratna Natalia Mendrofa; Netti Kariani Mendrofa (LPPM Institut Ahmad Dahlan Probolinggo, 2026)
from students’ everyday experiences. One approach considered capable of bridging this gap is ethnomathematics, a learning approach that integrates elements of local culture into mathematical concepts. This article aims to systematically examine the implementation of an ethnomathematics approach based on Nias culture in elementary school mathematics learning through a literature review.The method employed is a literature study of books, national and international journal articles, and relevant documents discussing ethnomathematics, Nias culture, and mathematics learning at the elementary school level. The results of the review indicate that Nias culture possesses rich ethnomathematical potential, evident in traditional architecture, carving patterns, number systems, traditional economic activities, and folk games. Integrating these cultural elements into elementary school mathematics learning can enhance students’ conceptual understanding, learning motivation, and foster appreciative attitudes toward local culture. This article recommends the development of mathematics learning tools based on Nias cultural ethnomathematics as an innovation for contextual learning in elementary schools.